Optimalisasi Kewirausahaan dan Kemitraan Strategis untuk Kemandirian Ekonomi Pesantren di Indonesia - Mukhammad Taufiqur Rakhman (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This policy paper describes that Islamic boarding schools (pesantren) play a strategic role in shaping the character and morals of Indonesia's young generation. However, despite the government's launch of various policies, such as the Islamic Boarding School Economic Independence Program through the Ministry of Religious Affairs, many Islamic boarding schools still face obstacles in implementing these programs. These obstacles generally relate to managerial capacity, access to capital, and limited business mentoring. Dependence on external funding, such as donations and aid, is a major challenge limiting the sustainability of pesantren operations. To address this issue, the development of productive business units and the enhancement of entrepreneurial capacity among pesantren administrators are necessary. This study analyzes the potential for economic independence through an entrepreneurial approach based on Islamic values and synergy with the local business sector. To improve managerial capacity, entrepreneurial training policies and the strengthening of relevant curricula in pesantren are required. The study's findings indicate that policies strengthening entrepreneurial capacity, developing pesantren cooperatives, and strategic partnerships with local industries are effective policy alternatives to improve pesantren's economic independence. These policies would allow pesantren to reduce dependence on donations and enhance their long-term operational sustainability.